The Equine Herpesvirus 1 IR6 Protein That Colocalizes with Nuclear Lamins Is Involved in Nucleocapsid Egress and Migrates from Cell to Cell Independently of Virus Infection - Osterrieder, Nikolaus (American Society for Microbiology, 1998)
The equine herpesvirus 1 (EHV-1) IR6 protein forms typical rod-like structures in infected cells, influences virus growth at elevated temperatures, and determines the virulence of EHV-1 Rac strains (Osterrieder et al., Virology 226:243–251, 1996). Experiments to further elucidate the functions and properties of the IR6 protein were conducted. It was shown that the IR6 protein of wild-type RacL11 virus colocalizes with nuclear lamins very late in infection as demonstrated by confocal laser scan microscopy and coimmunoprecipitation experiments. In contrast, the mutated IR6 protein encoded by the RacM24 strain did not colocalize with the lamin proteins at any time postinfection (p.i.). Electron microscopical examinations of ultrathin sections were performed on cells infected at 37 and 40°C, the latter being a temperature at which the IR6-negative RacH virus and the RacM24 virus are greatly impaired in virus replication. These analyses revealed that nucleocapsid formation is efficient at 40°C irrespective of the virus strain. However, whereas cytoplasmic virus particles were readily observed at 16 h p.i. in cells infected with the wild-type EHV-1 RacL11 or an IR6-recombinant RacH virus (HIR6-1) at 40°C, virtually no capsid translocation to the cytoplasm was obvious in RacH- or RacM24-infected cells at the elevated temperature, demonstrating that the IR6 protein is involved in nucleocapsid egress. Transient transfection assays using RacL11 or RacM24 IR6 plasmid DNA and COS7 or Rk(13) cells, infection studies using a gB-negative RacL11 mutant (L11ΔgB) which is deficient in direct cell-to-cell spread, and studies using lysates of IR6-transfected cells demonstrated that the wild-type IR6 protein is transported from cell to cell in the absence of virus infection and can enter cells by a yet unknown mechanism.